Phytochrome A enhances the promotion of hypocotyl growth caused by reductions in levels of phytochrome B in its far-red-light-absorbing form in light-grown Arabidopsis thaliana. - Casal, J J (1996)
We sought to determine if phytochrome B (phyB)-mediated responses to the red light (R)/far-red light (FR) ratio are affected by phytochrome A (phyA) activity in light-grown seedlings of Arabidopsis thaliana. Pulses of FR delayed into the dark period were less effective than end-of-day (EOD) FR in promoting hypocotyl growth over a given period in darkness. White light minus blue light interposed instead of darkness between the end of the white-light photoperiod and the FR pulse was sufficient to maintain responsivity to the decrease in phyB in FR-light-absorbing form in wild-type (WT) seedlings, but not in the phyA mutant. Compared with EOD R, hourly R+FR pulses provided throughout the night caused a stronger promotion of stem growth than a single EOD R+FR pulse in WT Arabidopsis, cucumber, mustard, sunflower, tobacco, and tomato, but not in phyA Arabidopsis or in the aurea mutant of tomato. WT seedlings of Arabidopsis responded to a range of high EOD R/FR ratios, whereas the phyA mutant required stronger reductions in the EOD R/FR ratio. In sunlight, phyA seedlings of Arabidopsis showed no response to the "early warning" signals of neighboring vegetation, and hypocotyl-growth promotion occurred at higher plant densities than in the WT. Thus, under a series of light conditions, the sensitivity or responsivity to reductions in the R/FR ratio were larger in WT than in phyA seedlings. A product of phyA is therefore proposed to enhance the hypocotyl-growth response to decreases in phyB in FR-light-absorbing form in light grown seedlings.